Growth Performance and Yield of Lettuce (Lactuca sativa L.) on Different Media in an NFT Hydroponic System - Youmandja Arif Riyak Thiombiano; Pangesti Nugrahani; Ramdan Hidayat (Department of Agronomy and Horticulture, IPB University, 2026)
The operational success of closed-loop hydroponic systems is largely governed by the synergistic selection of the cultivation substrate and crop variety. An optimal growing medium must provide reliable structural stability, uniform moisture retention, and localized nutrient accessibility, which, when coupled with a cultivar’s inherent genetic potential, dictate overall vegetative development and marketable yield. This study evaluated the effects of different growing media and lettuce cultivars on growth dynamics and yield performance in a nutrient film technique (NFT) system. The experiment was arranged in a two-factor completely randomized design, evaluating lettuce cultivars ‘Arroyo’, ‘Amaroza’, and ‘Espirando’ and growing substrates: rockwool, cocopeat, and peatmoss. The results revealed significant interaction effects between cultivar and growing media for plant height at 28 days after transplanting (DAT) and rosette canopy diameter at 7 DAT. The treatment combination integrating the cultivar ‘Arroyo’ with a peat moss substrate consistently yielded the highest values for these growth parameters. Furthermore, across all evaluated growing media, ‘Arroyo’ demonstrated superior biomass accumulation and overall productivity, highlighting its robust agronomic suitability for tropical NFT hydroponic cultivation.